The Relationship between Chronic Energy Deficiency in Pregnant Women and the Incidence of Low Birth Weight at the Senggo Health Center, Mappi Regency, Indonesia - Pairah Leda; Mikawati; Asriyanti; Muaningsih; Rizky Pratiwi (HM Publisher, 2023)
Globally, it is estimated that 15-20% of all births, or >20 million newborns each year, are low birth weight babies. Low and middle-income countries have a fairly high burden of LBW. The incidence of low birth weight in Papua is highest in the city of Jayapura. Namely, with a birth rate of 5,142 there are 169 incidents of LBW, while in Mappi city, with a birth rate of 2532, there are 80 incidents of low birth weight, and this is still quite high. This study is research descriptive analytics with a planned cross-sectional study. The population in this study is all patients with chronic energy deficiency at the Senggo Health Center were 61 respondents taken from January to February 2023 with a total sample of 53 obtained using simple random sampling. The results showed that there is a relationship between chronic lack of energy in pregnant women with the incidence of low birth weight at the Senggo Health Center with a value of p=0.007<< α=0.05. So it can be concluded that pregnant women who experience chronic energy deficiency will be at risk of giving birth to babies with low birth weight.